Rwanda's Gacaca courts between retribution and reparation - Bornkamm, Paul Christoph (Oxford : Oxford University Press, 2012)
The Gacaca courts are a traditional justice mechanism used by the Rwandan government to try lower-level perpetrators of the 1994 genocide. This book provides an empirical analysis of these courts, assessing their rules and procedures as well as their contribution to reconciliation in Rwanda.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Gacaca justice system; Trials (Genocide) -- Rwanda; Truth commissions -- Rwanda; Rwanda -- History -- Civil War, 1994 -- Atrocities